The relationship between intangible cultural heritage and community development: A case study of kite playing in Vietnam’s Red River Delta - Phuong Anh, Dang Thi (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Intangible cultural heritage plays an important role for people and local communities to develop a sense of identity. It is an expression of cultural diversity that can promote intellectual, emotional, and behavioral involvement on many levels, thus conveying a sense of heritage to the next generation. However, the growing influence of industrialization and personal autonomy in modern society may jeopardize some traditional practices. Local communities determine if intangible cultural heritage is worthwhile, typically basing their decisions on the benefits derived from participation (i.e., economic, environmental, social, and cultural). Safeguarding intangible cultural heritage is a two stage process: 1) intangible cultural heritage produces benefits for communities; and 2) communities develop a sense of identity from intangible cultural heritage. This case study on kite playing helps to prove the relationship between intangible cultural heritage and community development in Vietnam.Received: 13th March 2016; Revised:19th April 2017; Accepted 25th April 2017